Total Phenolic Content, Antioxidant Activity, Some Physical and Chemical Properties of Pestil - SENGÜL*, MEMNUNE; YILDIZ, HILAL; GÜNGÖR†, NEVA; OKÇU, ZÜHAL (Asian Journal of Chemistry, 2024)
The objective of the present investigation is to determine total phenoliccontent, antioxidant activity, some physical and chemical properties ofmulberry pestil (without additive, with glucose, with peanut, with walnut),plum pestil and cornelian cherry pestil. Total phenolic content of thewater extracts of pestil samples was estimated as gallic acid equivalents(GAE) by Folin-Ciocalteu method spectrophotometrically. The antioxidantactivity of water extracts prepared from pestil samples wasmeasured by β-carotene bleaching method. Total phenolic content wasfound from 4.79 (mulberry pestil without additive) to 28.36 μg GAE/mg(plum pestil). The antioxidant activity of pestil samples varied from40.05 % (mulberry pestil without additive) to 90.92 % (plum pestil).Dry matter, ash, protein, total sugar, reducing sugar, sucrose, pH, titratableacidity, colour (L, a, b), thickness of pestil samples were determinedbetween 75.30-87.53 %, 0.18-3.42 %, 2.44-7.35 %, 30.91-54.60 %,21.38-41.05 %, 0.83-27.54 %, 3.39-5.72 %, 0.06-6.25 % (malic acid);27.35-41.35, (+1.25)-(+11.50), (+0.99)-(+18.22), 0.57-6.40 mm, respectively.The present study shows that pestil samples had high amount ofphenolics content, antioxidant activity, carbohydrates and protein content.